From: sadoc on 28 May 2010 03:04 Dear All, Please, how can I solve the following recursion? x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i m / a ) x[ i - 1 ] ) - ( 1 / a ) Thanks! Best regards, Daniel
From: Robert Israel on 28 May 2010 04:04 sadoc <danielsadoc(a)gmail.com> writes: > Please, how can I solve the following recursion? > > x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i > m / a ) x[ i - 1 ] ) - ( 1 / a ) > Using the rsolve command in Maple 14, I get the following: x(i) = (1/a*m)^i*GAMMA(i+1)*(-1/a*(1-exp(a/m)*(1-a/m))+1/m*i/((1/a*m)^i)/GAMMA(i+2)*hypergeom([1, i+1],[i, i+2],a/m)) + x(0) * (1/a*m)^i*(GAMMA(i+1)*a+GAMMA(i+1)*m-exp(a/m)*GAMMA(i+1,a/m)*m)/a - x(1) * (1/a*m)^i*(GAMMA(i+1)-exp(a/m)*GAMMA(i+1,a/m)) I don't know if this can be simplified further. -- Robert Israel israel(a)math.MyUniversitysInitials.ca Department of Mathematics http://www.math.ubc.ca/~israel University of British Columbia Vancouver, BC, Canada
From: William Elliot on 28 May 2010 05:20 On Fri, 28 May 2010, sadoc wrote: > Please, how can I solve the following recursion? > > x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i > m / a ) x[ i - 1 ] ) - ( 1 / a ) Yicks. Is this what you wrote? x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) Besides needing to state a /= 0, it needs to be simplified. a.x[i + 1] = (a + (i + 1)m).x[i] - im.x[i - 1] - 1 A random thought occurs; a(x[i + 1] - x[i]) = (i + 1)m.x[i] - im.x[i - 1] - 1 a(x[i + 1] - x[i]) = im(x[i] - x[i - 1]) + m.x[i] - 1 Let's solve the case m = 0. a(x[i + 1] - x[i]) = -1; x[i + 1] = x[i] - 1/a For all i in N, x[i] = x[0] - i/a is the solution. Regards the case m /= 0, for all i in N, x[i] = x[0] = 1/m is a solution. Let's examine the case for all i, x[i + 1] - x[i] = t. at = imt + m.x[i] - 1; m.x[i] = at - imt + 1 For all i, x[i] = at/m + 1/m - it isn't a solution if t /= 0, because x[i + 1] - x[i] = -t, contrary to the assumption x[i + 1] - x[i] = t.
From: sadoc on 28 May 2010 11:20 Hi, thanks for the reply. Yes, the recursion I would like to solve is x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) I forgot to add the boundary conditions, though, x[1] = x[0]-1/a x[0] is unknown but x[infinity] = 1/m William, x[infinity]=1/m is in line with the solution you proposed. However, I would like to cope with the boundary condition x[1]=x[0]-1/ a Robert, using Maple, I was able to solve the recursion using rsolve({x(n)=(1+(n)*m/a)*x(n-1) - ((n-1)* m/a)*(x(n-2)) - 1/a, x(1)=x0-1/a, x(0)=x0}, x(n)); However, I get a very complicate solution, and I don't know how to cope with the condition x[infinity]=1/m The motivation to the problem I'm trying to solve is the following: consider a Markov chain with the following generator matrix q(i,i+1) = a (i>=0) q(i,i-1) = im (i>=1) q(i,-1) = m (i>=1) Question: given that we start in state s, s >=0, what is the mean time to reach state -1? I think that this is related to birth-death processes with killing... Thanks again! Best regards, Daniel On May 28, 5:20 am, William Elliot <ma...(a)rdrop.remove.com> wrote: > On Fri, 28 May 2010, sadoc wrote: > > Please, how can I solve the following recursion? > > > x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i > > m / a ) x[ i - 1 ] ) - ( 1 / a ) > > Yicks. Is this what you wrote? > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) > > Besides needing to state a /= 0, it needs to be simplified. > > a.x[i + 1] = (a + (i + 1)m).x[i] - im.x[i - 1] - 1 > > A random thought occurs; > a(x[i + 1] - x[i]) = (i + 1)m.x[i] - im.x[i - 1] - 1 > > a(x[i + 1] - x[i]) = im(x[i] - x[i - 1]) + m.x[i] - 1 > > Let's solve the case m = 0. > > a(x[i + 1] - x[i]) = -1; x[i + 1] = x[i] - 1/a > > For all i in N, x[i] = x[0] - i/a is the solution. > > Regards the case m /= 0, > for all i in N, x[i] = x[0] = 1/m > is a solution. > > Let's examine the case for all i, x[i + 1] - x[i] = t. > > at = imt + m.x[i] - 1; m.x[i] = at - imt + 1 > > For all i, > x[i] = at/m + 1/m - it > isn't a solution if t /= 0, because > x[i + 1] - x[i] = -t, > contrary to the assumption > x[i + 1] - x[i] = t.
From: Ray Vickson on 28 May 2010 13:14 On May 28, 8:20 am, sadoc <danielsa...(a)gmail.com> wrote: > Hi, > > thanks for the reply. Yes, the recursion I would like to solve is > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) For your future reference: your equation is still unnecessarily hard to read. You should strip off the brackets around separate terms and just write x[i + 1] = ((a + (i + 1)m)/a).x[i] - (im/a).x[i - 1] - 1/a. As long as you leave spaces around the separate terms, the '+' and '-' signs will serve to delimit the different terms. Also, you might try mixing bracket types when submitting equations written in ASCII, so it would be even better to write x[i + 1] = {[a + (i + 1)m]/a}.x[i] - (im/a).x[i - 1] - 1/a. Do you see how much clearer that is? R.G. Vickson > > I forgot to add the boundary conditions, though, > > x[1] = x[0]-1/a This is a problem: if you put i=0 in the recursion (and assume x[-1] is not infinite) you get x[1] = x[0]*(a+m)/a - 1/a. In order to have x[1] = x[0] - 1/a you need (a+m)/a = 1, hence m = 0. So, either the recursion fails for i = 0 or your boundary condition is wrong. R.G. Vickson > > x[0] is unknown but > > x[infinity] = 1/m > > William, x[infinity]=1/m is in line with the solution you proposed. > However, I would like to cope with the boundary condition x[1]=x[0]-1/ > a > > Robert, using Maple, I was able to solve the recursion using > > rsolve({x(n)=(1+(n)*m/a)*x(n-1) - ((n-1)* m/a)*(x(n-2)) - 1/a, > x(1)=x0-1/a, x(0)=x0}, x(n)); > > However, I get a very complicate solution, and I don't know how to > cope with the condition x[infinity]=1/m > > The motivation to the problem I'm trying to solve is the following: > > consider a Markov chain with the following generator matrix > > q(i,i+1) = a (i>=0) > q(i,i-1) = im (i>=1) > q(i,-1) = m (i>=1) > > Question: given that we start in state s, s >=0, what is the mean time > to reach state -1? > > I think that this is related to birth-death processes with killing... > > Thanks again! > > Best regards, Daniel > > On May 28, 5:20 am, William Elliot <ma...(a)rdrop.remove.com> wrote: > > > On Fri, 28 May 2010, sadoc wrote: > > > Please, how can I solve the following recursion? > > > > x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i > > > m / a ) x[ i - 1 ] ) - ( 1 / a ) > > > Yicks. Is this what you wrote? > > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) > > > Besides needing to state a /= 0, it needs to be simplified. > > > a.x[i + 1] = (a + (i + 1)m).x[i] - im.x[i - 1] - 1 > > > A random thought occurs; > > a(x[i + 1] - x[i]) = (i + 1)m.x[i] - im.x[i - 1] - 1 > > > a(x[i + 1] - x[i]) = im(x[i] - x[i - 1]) + m.x[i] - 1 > > > Let's solve the case m = 0. > > > a(x[i + 1] - x[i]) = -1; x[i + 1] = x[i] - 1/a > > > For all i in N, x[i] = x[0] - i/a is the solution. > > > Regards the case m /= 0, > > for all i in N, x[i] = x[0] = 1/m > > is a solution. > > > Let's examine the case for all i, x[i + 1] - x[i] = t. > > > at = imt + m.x[i] - 1; m.x[i] = at - imt + 1 > > > For all i, > > x[i] = at/m + 1/m - it > > isn't a solution if t /= 0, because > > x[i + 1] - x[i] = -t, > > contrary to the assumption > > x[i + 1] - x[i] = t. > >
|
Next
|
Last
Pages: 1 2 Prev: Godels seconded theorem ends in paradox-simple proof Next: Is this function convex? |